Statistics without maths for psychology - Dancey, Christine P. (Pearson, 2017)
Highly praised for its clear, straightforward approach, Statistics without Maths for Psychology&​#x00A0;7th edition provides a comprehensive and accessible introduction to statistics and SPSS. This widely used and trusted textbook is packed with examples, activities and questions to help you to test your learning and deepen your understanding in a practical and manageable way.&​#x00A0; &​#x00A0; Statistics without Maths for Psychology, 7e, will help you to gain the confidence to apply statistical concepts and use SPSS to analyse data within your studies and future independent research.